Earth tomography with atmospheric neutrino oscillations - D'Olivo, Juan Carlos (2020)
The study of the flux of atmospheric neutrino crossing the Earth can provide useful information not only on the matter density of the different layers that make up the planet but also on their chemical composition. The key phenomenon that makes this possible is flavor oscillations and their dependence on the electron density along the neutrino baseline. To extract the relevant information, we simulate the energy and azimuth angle distribution of events produced in a generic neutrino telescope by atmospheric neutrinos passing through the deepest parts of the Earth. Changes in the densities of the outer core and the mantle are implemented by varying the location of the boundary between these layers so that the restrictions on the mass of and the moment of inertia of the Earth are both satisfied. This allows us to examine the effect of simultaneous changes in composition and density of the outer core, unlikely other works on the subject, where only one of these quantities was varied.